2015
DOI: 10.1242/bio.015263
|View full text |Cite
|
Sign up to set email alerts
|

Apical constriction and epithelial invagination are regulated by BMP activity

Abstract: Epithelial invagination is a morphological process in which flat cell sheets transform into three-dimensional structures through bending of the tissue. It is accompanied by apical constriction, in which the apical cell surface is reduced in relation to the basal cell surface. Although much is known about the intra-cellular molecular machinery driving apical constriction and epithelial invagination, information of how extra-cellular signals affect these processes remains insufficient. In this study we have esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 58 publications
(107 reference statements)
3
32
0
Order By: Relevance
“…This contact is established by the constraining effects of ECM [123] and the formation of F-actin-rich basal temporal filopodia acting as physical tethers [124]. This model was further extended by findings which showed that the ECM causes lens cells to thicken locally in order to facilitate subsequent invagination [99, 125], a process primarily driven by both apical constriction to produce wedge-shaped cells [122, 126] and by BMP signaling [127]. In the invaginating lens placode, the cells near the lens pit circumferentially contract the adherens junctional complexes joining them together, and this actomyosin cytoskeleton remodeling requires RhoA small GTPase, Rho-kinase (Rock), PDZ domain-containing protein Shroom3, and p120-catenin δ1 [122, 126].…”
Section: Lens Morphogenesis and Gene Regulatory Networkmentioning
confidence: 99%
“…This contact is established by the constraining effects of ECM [123] and the formation of F-actin-rich basal temporal filopodia acting as physical tethers [124]. This model was further extended by findings which showed that the ECM causes lens cells to thicken locally in order to facilitate subsequent invagination [99, 125], a process primarily driven by both apical constriction to produce wedge-shaped cells [122, 126] and by BMP signaling [127]. In the invaginating lens placode, the cells near the lens pit circumferentially contract the adherens junctional complexes joining them together, and this actomyosin cytoskeleton remodeling requires RhoA small GTPase, Rho-kinase (Rock), PDZ domain-containing protein Shroom3, and p120-catenin δ1 [122, 126].…”
Section: Lens Morphogenesis and Gene Regulatory Networkmentioning
confidence: 99%
“…For instance, Rho GTPase [17] and p120 catenin [13] are required to localize myosin II apically in the cell. BMP, acting upstream of Rock in chick otic placode (neuroepithelial) invagination, seems to be required for apical localization of actin independently of a role in cell type specification [23].
Figure 1.Classical apical constriction.
…”
Section: Apical Constrictionmentioning
confidence: 99%
“…Another possibility is that Bmp2 rescues the F-actin tension by modulating the expression of other non-conventional myosins that are not inhibited by BDM. Indeed, Bmp signaling has been recently shown to regulate epithelial morphogenesis by controlling F-actin rearrangements, apical constriction, cell elongation and epithelial bending 78 . Along this line, interkinetic nuclear migration during morphogenesis of the retina is driven by actomyosin forces that are blocked when myosin II is inhibited, and the reduction in the velocity of migration and cytoskeleton dynamics by BDM can be rescued by BDM-insensitive myosins 79 .…”
Section: Discussionmentioning
confidence: 99%